Lectori salutem; Tartalomjegyzék - Búr, Gábor; Tarrósy, István (Afrika Tanulmányok / Hungarian Journal of African Studies, 2022)
Dear Readers, The first issue of Vol. 16 is a collection of many intriguing papers. First, based on field research conducted in May 2021, Gergely Buda presents seven Ugandan businesses and entrepreneurs which apply circular economy practices in their operations. The examples touch on plastic recycling, agriculture, carpentry, textile, and paper and packaging industries. Second, using a political ecology perspective, Rashed Daher’s article seeks to understand the origin of water problems in Egypt, and argues that beyond existing scarcity due to environmental challenges, current sociopolitical conditions play a significant role. Third, Judit Kiss deals with the controversial role of external financial resources in Africa. She concludes that not the external world finances Africa, but Africa finances the world. The issue of financing Africa’s development cannot be solved without (a) mobilizing domestic resources (including domestic savings), (b) attracting external resources as well as improving the use and avoiding the misuse of inflowing financial resources, and (c) curbing capital flight and tackling illicit financial outflow. Fourth, again based on a series of field research, Robert Kłosowicz looks at the ‘Western Sahara question’ from the perspective of Mauritania, which is in quite a difficult position as it attempts to not become conflicted with either of its powerful neighbours, both of which are aspiring to be leaders in the region. Fifth, Alfred Babo, based on ethnographic research in the Moshi District, argues that beyond changes induced by the ethical business organization, local coffee-growing farmers are trapped in “darkness” due to having insufficient information on their trading partner and limited ability to empower and transform their cooperatives. Finally, we offer a review of fresh insight into the impact of Covid-19 on higher education worldwide, but with a peculiar focus on African countries. Dr. Gábor Búr and Dr. István Tarrósy editor-in-chiefs